2005
DOI: 10.1086/431588
|View full text |Cite
|
Sign up to set email alerts
|

Improved Diagnosis of the Etiology of Community-Acquired Pneumonia with Real-Time Polymerase Chain Reaction

Abstract: The combined real-time PCR assay is more sensitive for diagnosis of the main viruses and atypical bacteria that cause CAP compared with conventional methods, and obtains results in a clinically relevant time period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
260
6
18

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(307 citation statements)
references
References 42 publications
23
260
6
18
Order By: Relevance
“…For instance, some (but not all) studies included in our meta-analysis showed higher severity of pneumonia with bacterial and viral co-infection [1,20]. The interaction seems particularly relevant with rhinovirus [1,8] and influenza [44].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…For instance, some (but not all) studies included in our meta-analysis showed higher severity of pneumonia with bacterial and viral co-infection [1,20]. The interaction seems particularly relevant with rhinovirus [1,8] and influenza [44].…”
Section: Discussionmentioning
confidence: 76%
“…The most commonly identified viruses were influenza in 18 studies [3, 6, 7, 10, 11, 17-19, 21, 23, 26, 27, 29, 31, 32, 34-36], rhinovirus in eight studies [1,5,8,12,22,24,25,28], respiratory syncytial virus in three studies [2,9,33] and coronavirus in two studies [20,30]. Meta-analyses revealed that the proportion of infection by influenza (31 studies) was 8% (95% CI 6.3-9.6%; I 2 =91.9%), by rhinovirus (25 studies) was 5.7% (95% CI 4.3-7.1%; I 2 =90.3%), by respiratory syncytial virus (29 studies) was 2.2% (95% CI 1.6-2.8%; I 2 =80%) and by coronavirus (18 studies) was 3.3% (95% CI 2.3-4.2%; I 2 =80.2%).…”
Section: Individual Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Además, las muestras congeladas y descongeladas pueden reducir la sensibilidad de la PCR. Coincidentemente, en el mismo estudio de Templeton, aquellos casos sin diagnóstico eran un grupo oligosintomático, lo que pudiera estar asociado a menor carga viral y menor rendimiento de test diagnósticos 10 . Esto se asemeja a nuestros pacientes con RT-PCR (-) ya que en ellos se identifi caron algunos elementos que sugieren formas más leves: hospitalización más breve, ausencia de SDRA, menor requerimiento de UCI y VM.…”
Section: Discussionunclassified
“…Rapid diagnostic methods help to avoid inadequate antimicrobial treatment and support infection control interventions to limit nosocomial infections . Molecular methods demonstrate greater sensitivity than conventional assays for detecting adenovirus in respiratory samples 11,12 . Brazilian studies have described HAdV frequencies of 3 to 7.1%, as measured using different diagnostic techniques [13][14][15][16] .…”
Section: Human Adenovirus Detection Among Immunocompetent and Immunocmentioning
confidence: 99%